2020
DOI: 10.1371/journal.pone.0241338
|View full text |Cite
|
Sign up to set email alerts
|

Baseline gut microbiome composition predicts metformin therapy short-term efficacy in newly diagnosed type 2 diabetes patients

Abstract: Background The study was conducted to investigate the effects of metformin treatment on the human gut microbiome’s taxonomic and functional profile in the Latvian population, and to evaluate the correlation of these changes with therapeutic efficacy and tolerance. Methods In this longitudinal observational study, stool samples for shotgun metagenomic sequencing-based analysis were collected in two cohorts. The first cohort included 35 healthy nondiabetic individuals (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 64 publications
2
36
2
Order By: Relevance
“…We also found that the abundances of norank_f_Ruminococcaceae and unclassified_f_Ruminococcaceae were reduced by metformin. Elbere et al have shown that the metformin treatment can elevate the abundance of Oscillibacter in both healthy nondiabetic individuals and T2DM patients ( Elbere et al, 2020 ), which is opposite to our results. The alteration of Lactobacillus in our present work was also inconsistent with previous findings, in which its abundance is increased by metformin treatment in obese or diabetic rodents ( Zhang et al, 2015 ; Zhang M. et al, 2019 ; Cui et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 99%
“…We also found that the abundances of norank_f_Ruminococcaceae and unclassified_f_Ruminococcaceae were reduced by metformin. Elbere et al have shown that the metformin treatment can elevate the abundance of Oscillibacter in both healthy nondiabetic individuals and T2DM patients ( Elbere et al, 2020 ), which is opposite to our results. The alteration of Lactobacillus in our present work was also inconsistent with previous findings, in which its abundance is increased by metformin treatment in obese or diabetic rodents ( Zhang et al, 2015 ; Zhang M. et al, 2019 ; Cui et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Elbere et al and Sun et al found that metformin clinical benefits are partly mediated by bacteria-specific mechanisms such as glucose-SGLT1-sensing glucoregulatory pathway associated with Lactobacillus increase or B. fragilis —glycoursodeoxycholic acid (GUDCA)—intestinal farnesoid X receptor (FXR) [ 65 , 66 ]. Furthermore, higher abundances of Enterococcus faecium , Lactococcus lactis , Odoribacter , and Dialister were linked to a better response to metformin, while higher Prevotella copri suppresses it [ 65 ]. Based on these studies, microbiome preparation with proven gut-modulating interventions could improve response to first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Those cases could express a more severe diabetic phenotype compared to the untreated diabetes cases. However, previous studies have reported that metformin use itself affects gut microbiome composition, even in healthy normoglycemic individuals [ 9 , 22 , 23 , 24 , 59 , 60 ]. Therefore, disentangling the effect of metformin from the effect of type 2 diabetes on the gut microbiome in our datasets is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, of all ASVs associated to Met-T2D in both ethnicities, almost all have been related to metformin use before in humans with the same direction. Clostridium sensu stricto 1 [ 23 ] and Peptostreptococcaceae Romboutsia [ 24 ], Terrisporobacter [ 23 ], and especially Intestinibacter bartlettii [ 9 , 22 , 23 , 60 ] were decreased, while Escherichia [ 9 , 22 , 23 , 24 ] showed an increase after metformin treatment in previous studies. In our study, Romboutsia was identified as a robust and strong biomarker in the relation between Met-T2D and the gut microbiome in both ethnicities.…”
Section: Discussionmentioning
confidence: 99%